Y-(-2)=6/1(x-2)

Simple and best practice solution for Y-(-2)=6/1(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-(-2)=6/1(x-2) equation:


x in (-oo:+oo)

Y+2 = (6/1)*(x-2) // - (6/1)*(x-2)

Y-((6/1)*(x-2))+2 = 0

Y-6*(x-2)+2 = 0

Y-6*(x-2)+2 = 0

Y-6*x+2+12 = 0

Y-6*x+14 = 0

Y-6*x+14 = 0

Y-6*x+14 = 0 // - Y+14

-6*x = -(Y+14) // : -6

x = (-(Y+14))/(-6)

x = (Y+14)/6

x = (Y+14)/6

See similar equations:

| 10+12=14y-1-13y | | 3.25g+1.25g=81 | | 15X+4=10X+21 | | ay=5y+16 | | 12d=11 | | 15-3(x+5)-2= | | c-13=-1 | | 4(3p+2)-5(6p-1)=2(p-8)-6(7p-4) | | 6+4(x-1)+8= | | -12+8+(-2)= | | 5(x+4)-10= | | -2x-5=-2+1 | | 16p+14q= | | https://media.education2020.com/evresources/3108-05-05/mc018-1.jpg | | 3(x-1)+7= | | 9x-27=6x+12 | | -3+11=10y-13-19y | | (6x+2)-16=0 | | 8c-4/6c-3 | | 9x^2-24x-65=0 | | -7/3×n=-42 | | logx=2.45 | | -42-32r= | | 23+21z= | | B*8=96 | | -11v= | | 48=8-10n | | s^2+15s+20=0 | | 10x+5x-3x=120 | | 1+20xX=Y | | 4x-10x=14 | | .375x-13=-25 |

Equations solver categories